Managing global cyber security implementation project using PMI methodology in a manufacturing company - Jefrey, Ruvimbo (Univerzita Pardubice, 2019)
Cybersecurity has been an important topic to most organizations in the 21st- century. Billions of dollars have been lost through cybersecurity and its threats. Various organization are tightening their security programs using various methodologies. The PMI approach focus on a well laid down plan by the Project Management Institude on implementing project within organizations. This study thus use the PM Methodology to implement cybersecurity in Foxconn a manufacturing company. The main goal of this thesis is to identify the methods that are used to managing cybersecurity implementation project using PMI methodology in a manufacturing company. This has been achieved by conducting a semi-structured analysis of some of the methodologies that companies over the years have adopted in implementing their projects with much focus on the PM methodology.
Keywords: kybernetická bezpečnost; metodika PM; životní cyklus projektu; cybersecurity; PM methodology; project life cycle